2010
DOI: 10.1007/s12008-010-0089-1
|View full text |Cite
|
Sign up to set email alerts
|

Integration and evaluation of haptic feedbacks: from CAD models to virtual prototyping

Abstract: This paper studies the benefits that haptic feedback can provide in performing complex maintenance tasks using virtual mock-ups. We have carried out user study that consisted on two experiments where participants had to perform an accessibility task. A human-scale string-based haptic interface was used to provide the operator with haptic stimuli. A prop was used to provide grasp feedback. A mocap system tracks user's hand and head movements while a 5DT data-glove is used to measure finger flexion. In the first… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…Several authors have developed VAPs using different assembly techniques, such as feature matching recognition (Iacob et al, 2011;Sato et al, 2011), constrained based modelling Gutiérrez et al, 2010;Tching et al, 2010), PBM (Gupta et al, 1997;Lim et al, 2007;Garbaya and Zaldivar-Colado, 2009;Chamaret et al, 2010;Aleotti and Caselli, 2011;Xia et al, 2012), import of CAD assembly constraints (Jayaram et al, 1999;Chen et al, 2010;Cheng-jun et al, 2010), and the use of haptics (Ritchie et al, 2008b;Bordegoni et al, 2009;Ladeveze et al, 2010;Liu et al, 2010;Ji et al, 2011;Christiand and Yoon, 2011). Some of these systems are summarized in Table I.…”
Section: Virtual Assembly Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several authors have developed VAPs using different assembly techniques, such as feature matching recognition (Iacob et al, 2011;Sato et al, 2011), constrained based modelling Gutiérrez et al, 2010;Tching et al, 2010), PBM (Gupta et al, 1997;Lim et al, 2007;Garbaya and Zaldivar-Colado, 2009;Chamaret et al, 2010;Aleotti and Caselli, 2011;Xia et al, 2012), import of CAD assembly constraints (Jayaram et al, 1999;Chen et al, 2010;Cheng-jun et al, 2010), and the use of haptics (Ritchie et al, 2008b;Bordegoni et al, 2009;Ladeveze et al, 2010;Liu et al, 2010;Ji et al, 2011;Christiand and Yoon, 2011). Some of these systems are summarized in Table I.…”
Section: Virtual Assembly Systemsmentioning
confidence: 99%
“…Oriented to assembly sequence planning; optimal assembly algorithm for haptic guidance (Hassan and Yoon, 2010) Single Phantom Omni CAD-to-VR Human scale virtual environment; study the effects of haptic feedback in virtual assembly (Chamaret et al, 2010) SPIDAR, one hand IMA-VR Virtual training; combines haptic, gestures and visual feedback; parts with dynamic behaviour (Gutié rrez et al, 2010) Phantom Omni, LHIfAM or GRAB…”
Section: Mad Simulatormentioning
confidence: 99%
“…Haptic interface, as a promising 3D HCI for various applications, could allow the user to feel the contact force in the process of free-form design and more realistically convey virtual reality to humans so as to aid the design process [110][111][112]. To construct more immersive design environments for users, Damien Chamaret [113] and Simon Kind [114] combined haptic and VR in multimodal systems and found that haptic feedback can provide a more accurate manipulation of virtual objects and significantly improve the working efficiency of CAD systems. On this basis, a novel multimodal application, "VRSolid", was proposed by Mogan [73], further extending the input modalities within the VR environment.…”
Section: Other Interfaces For Cadmentioning
confidence: 99%
“…For example, the improvement of user performance associated with task repetitions was used to evaluate learnability in [113], including the task completion time and number of collisions. Meanwhile, Chu et al [117] focused on the number of design steps for modeling and the idle time period when the user knows exactly what to do and is planning how the interaction approach may be performed to achieve the design tasks.…”
mentioning
confidence: 99%
“…Several authors have developed VA systems using different methodologies such as automatic feature matching recognition (Iacob et al, 2011;Sato et al, 2011;Vigano and Osorio-Gó mez, 2012;Xu et al, 2012); constrained motion (Tching et al, 2010;Gutiérrez et al, 2010;Xia et al, 2012); reuse of CAD assembly constraints (Jayaram et al, 1999;Chamaret et al, 2010;Chen et al, 2010;Cheng-jun et al, 2010); physics-based modelling (PBM) (Garbaya and Zaldivar-Colado, 2009;Gupta et al, 1997;Aleotti and Caselli, 2011;Wan et al, 2004;Seth et al, 2006;Lim et al, 2007a); hybrid approaches (Seth, 2007;Xia et al, 2011); and the use of haptic feedback (Coutee et al, 2001;Ji et al, 2011;Christiand and Yoon, 2011;Ladeveze et al, 2010;Liu et al, 2010;Bordegoni et al, 2009;Lim et al, 2007a, b). A brief description of the main characteristics of these platforms is presented in Table I.…”
Section: Virtual Assemblymentioning
confidence: 99%